New Product Development (NPD) Process in Subsidiary: Information Perspectives - Firmanzah, Firmanzah (UI Scholars Hub, 2008)
Information is an important resource for new product development (NPD) process in subsidiary. However, we still lack of research to analyze NPD process from information perspective in subsidiary context. This research is an exploratory research and it exploited 8 cases of NPD process in consumer goods subsidiaries operating in Indonesian market. Three types of information have been identified and analyzed NPD process; global, regional and local information. The result of this research reveals that new product will be resulted is determined by the type of information used. This research reveals four new product typology using information types. The semi-structured interview and archive studies generate global, regional, integrated and local NPD process. Each process has its own characteristics such as type of information used and interaction pattern among subsidiary-regional office-headquarter.